OPTIMIZATION OF METHODS FOR THE PREVENTION AND TREATMENT OF ALVEOLITIS - Olimov Azimjon Bahromovich; Abdualimov Doniyor Mukhitdinovich (Web of Journals Publishing, 2025)
The aim of this study was to evaluate the effectiveness of using collagen coatings in combination with antibacterial agents in the treatment of purulent complications after tooth extraction. The study involved patients divided into three groups: the main group (MG), which received treatment using Alvostaz and collagen coatings, and two control groups: CG-1 — treated with a standard paste based on eugenol and iodoform, and CG-2 — treated with the collagen sponge "Collost®". The results showed that treatment in the main group was more effective, characterized by lower pain intensity, faster wound healing, and reduced inflammation compared to the control groups.
Keywords: Alveolitis, collagen coatings, antibacterial drugs, wound healing, treatment of purulent complications, postoperative period, anti-inflammatory treatment, wound exudate, pain syndrome.